2005
DOI: 10.1111/j.1439-054x.2005.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchitis bei Kindern unter Belastung durch Strassenverkehrslarm und Abgase. Bronchitis in Children Exposed to Road Traffic Noise and Exhaust Fumes

Abstract: ZusammenfassungFragestellung Wird die Häufigkeit von Bronchitis bei Kindern unter nächtlicher Belastung mit Straßenverkehrslärm erhöht? Welche Bedeutung haben dabei lärmbedingte Erhöhungen von Cortisol in der ersten Nachthälfte? Methodik Aus den Teilnehmern einer Beobachtungsstudie wurden 68 Kinder mit bzw. ohne Bronchitisbefund sowie mit niedriger bzw. hoher Verkehrslärmbelastung ausgewählt. Die Verkehrslärm-und Stickstoffdioxid-Belastung wurde vor repräsentativen Kinderzimmerfenstern gemessen. Auf der Grundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…As an initial step, understanding how metabolomic profiles vary by biological matrices in the same individuals may inform future study designs in this exposure science subfield. Non-invasive sampling of exhaled breath (EBC) [12,26] and saliva [27] may serve as viable alternatives to more invasive blood sampling. Comparative metabolomic profiling across the plasma, EBC, and saliva matrices may assist with the identification of the most relevant components of PM exposure for health.…”
Section: Introductionmentioning
confidence: 99%
“…As an initial step, understanding how metabolomic profiles vary by biological matrices in the same individuals may inform future study designs in this exposure science subfield. Non-invasive sampling of exhaled breath (EBC) [12,26] and saliva [27] may serve as viable alternatives to more invasive blood sampling. Comparative metabolomic profiling across the plasma, EBC, and saliva matrices may assist with the identification of the most relevant components of PM exposure for health.…”
Section: Introductionmentioning
confidence: 99%
“…Some relevant studies, i.e., the study of chronic noise exposure and hypertension in the Netherlands, reported a correlation coefficient of 0.72 between modeled noise and modeled annual average Particulate Matter10 (de Kluizenaar et al, 2007). A study in Germany reported a strong correlation (r=0.84) between measurements of night-time (0:00-6:00) traffic noise and 58-93 h measurements of NO2 at 25 locations (Ising et al, 2004).…”
Section: Correlation Between Air and Noise Pollution Due To Environme...mentioning
confidence: 99%
“…A total of 25 studies were identified that reported on the impact of noise exposure on cortisol levels [Table S5][ 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 ]; however the majority of studies ( n = 21) could not be pooled into a meta-analysis due to differences in populations, measurement of exposures, measurement of outcomes, and reporting of outcomes. Therefore, the results are presented narratively in the summary of findings table.…”
Section: R Esultsmentioning
confidence: 99%
“…Therefore, the results are presented narratively in the summary of findings table. [ 19 20 21 22 23 24 25 26 27 28 29 31 32 33 34 35 36 40 41 42 43 ] Concerns with risk of bias due to confounding, exposure assessment, missing data, and measurement of outcomes were identified [Tables S6 and S7]. As shown in Table 3 , there was very low CoE for the effects of increased noise exposure on cortisol levels.…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation